Cyclic behaviour of bolted shear connectors in steel-concrete composite beams. (1st November 2019) - Ataei, Abdolreza; Zeynalian, Mehran; Yazdi, Yahya
Highlights: Cyclic behaviour of steel-concrete composite connection is experimentally investigated. Steel-concrete composite connections have high ductility and energy dissipating capacity. Three different modes of failure were observed in the steel-concrete composite connections. The strength deterioration in cyclic loading is much higher than that in monotonic loading. Increasing the diameter and strength of the shear connector resulted in an increase in the hysteretic loop area. Abstract: An experimental study of the cyclic behaviour of steel-concrete composite connections using mechanical shear connectors subjected to a low-cycle high-amplitude loading regime is presented in this study. The ductility, strength degradation and absorbed energy which characterise the performance of a mechanical shear connector under cyclic loading conditions in steel-concrete composite connections are assessed. Nine steel-concrete composite connection specimens were designed and tested in order to investigate the cyclic behaviour of the proposed composite connections, and to elucidate the structural behaviour of the demountable bolt shear connectors between the precast concrete panels and steel beams. In addition, three monotonic tests on steel-concrete composite connection were conducted to evaluate the yield slip, yield load, ultimate slip, and ultimate shear strength capacity. The size of the bolted shear connector and the strength of the bolted shear connectors are the main variables in this study. The preparation and construction of the specimens, the testing procedure, the test set-up, and the instrumentation used are described and the results of the monotonic and cyclic tests are reported in detail.